REQUIREMENTS FOR THE DESIGN OF AN AUTO PARTS STORE - Ikromov Nurillo Avazbekovich; Teshaboyev Fayoziddin Shoxobiddin o`g`li; Abdulazizov Avazbek Shuhratbek o`g`li (Лучшие интеллектуальные исследования, 2023)
Abstract: Auto spare parts are a very popular and popular product, which clearly indicates what is in demand among the population of megacities. However, it should be understood that even such a high need does not guarantee automatic success for an entrepreneur. Only those who do not rest on their laurels, constantly analyze the interests of customers, develop and improve their business, can achieve their goals and take their place.